Contribution self efficacy and independent learning math toward students' mathematics learning outcomes - Chici Pratiwi; Neviyarni Neviyarni; Solfema Solfema (Fakultas Ilmu Pendidikan UNP)
Students’ experiencing problems on mathematics learning outcomes at school and many students who did not complete the study of mathematics. Self-efficacy and independent learning math is suspected of influencing factors. This study aimed to examine the contribution of self-efficacy, independent learning math mathematics on learning outcomes. The approach of this research was quantitative with correlational method. The population of this research consists samples 305 and 173 students. The instrument used a Likert scale model. Data were Analyzed using multiple regression. The results showed that there is a contribution of self-efficacy and independent learning math to mathematics learning outcomes.